Introducing Translation Studies Theories and Applications - Munday, Jeremy; Pinto, Sara Ramos; Blakesley, Jacob (Routledge, 2022)
Introducing Translation Studies remains the definitive guide to the theories and concepts that make up the field of translation studies. Providing an accessible and up-to-date overview, it has long been the essential textbook on courses worldwide. This fifth edition has been fully revised and continues to provide a balanced and detailed guide to the theoretical landscape. Each theory is applied to a wide range of languages, including Bengali, Chinese, English, French, German, Italian, Punjabi, Portuguese and Spanish. A broad spectrum of texts is analysed, including the Bible, Buddhist sutras, Beowulf, the fiction of Proust and the theatre of Shakespeare, European Union and UNESCO documents, a range of contemporary films, a travel brochure, a children's cookery book and the translations of Harry Potter. Each chapter comprises an introduction outlining the translation theory or theories, illustrative texts with translations, case studies, a chapter summary and discussion points and exercises. New features in this fifth edition include: new material to keep up with developments in research and practice. This includes the sociology of translation chapter, where a new case study employs a Bourdieusian approach. There is also newly structured discussion on translation in the digital age, audiovisual and machine translation revised discussion points and updated figures and tables new, in-chapter activities with links in the enhanced e-book to online materials and articles to encourage independent research an extensive updated companion website with video introductions and journal articles to accompany each chapter, online exercises, an interactive timeline, weblinks, and PowerPoint slides for teacher support This is a practical, user-friendly textbook ideal for students and researchers on courses in Translation and Translation Studies.